124k views
0 votes
−3(2a−14)−3a=24
what is a

User Vitorlui
by
4.8k points

1 Answer

3 votes

♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️


- 3(2a - 14) - 3a = 24


- 6a + 42 - 3a = 24


- 9a + 42 = 24

Subtract sides 42


- 9a + 42 - 42 = 24 - 42


- 9a = - 18

Divide sides by - 9


( - 9a)/( - 9) = ( - 18)/( - 9) \\


a = 2

_________________________________

CHECK :


- 3(2(2) - 14) - 3(2) = 24


- 3(4 - 14) - 6 = 24


- 3( - 10) - 6 = 24


30 - 6 = 24


24 = 24

Thus the solution is correct.....

♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️

User Mangaldeep Pannu
by
4.7k points